Senior house officers and their training. II. Perceptions of service and training. Issue 6710 (18th November 1989) - Grant, J.; Marsden, P.; King, R. C.
Abstract : Aspects of teaching and learning at senior house officer level in South East Thames region were investigated by analysis of the responses of consultants, senior registrars, registrars, and senior house officers to a postal questionnaire. Responses to sections about who teaches senior house officers, how senior house officers learn, and the relation between the service and training elements of these posts varied significantly, according to the status of the respondents; certain grades commonly overestimated their own contribution when compared with the estimates of the other grades. Although the replies of senior house officers showed that they were taught by various grades, 47% of this group did not regard the consultant as their main teacher. Senior registrars and registrars rather than consultants were regarded by senior house officers as best at teaching (63% v 48% respectively). Consultants and registrars were considered to require more commitment to training, personal educational training, and to be more approachable. Inquiry about teaching methods used most by senior house officers showed absence of a systematic approach to training. Only about half of senior house officers cited ward rounds with consultants. Views on the relation between training and service were significantly different among grades, but there was general dissatisfaction. Overall, the findings disclosed the ineffectiveness of senior house officer training posts. This arises from lack of a clear distinction between training and service elements, of educational training for teachers, of a clear contractual obligation to teach im the consultant grade, and of allotted time for training and study for the teachers and senior house officers respectively. Reversal of these current trends is needed for senior house officer posts to fulfil their main training function.